2007
DOI: 10.1103/physrevlett.99.045701
|View full text |Cite
|
Sign up to set email alerts
|

Ice Crystallization Induced by Optical Breakdown

Abstract: Ice crystallization in supercooled water has been initiated by focused Nd:YAG laser pulses at 1064 nm wavelength. The pulses of 8 ns duration and up to 2 mJ energy produce a bubble in the supercooled liquid after optical breakdown and plasma formation. The subsequent collapse and disintegration of the bubble into fragments was observed to be followed by ice crystal nucleation in many, but not all cases. Details of the crystallization events have been investigated by high-speed imaging, and nucleation statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…The probability of a primary nucleation can be increased by electrofreezing, where a high electrical field is locally applied to a sample [70,76]. Other physical methods to control nucleation include the use of ultrasound [82] or laser light pulses [83], reviewed elsewhere [73].…”
Section: Nucleation Temperaturementioning
confidence: 99%
“…The probability of a primary nucleation can be increased by electrofreezing, where a high electrical field is locally applied to a sample [70,76]. Other physical methods to control nucleation include the use of ultrasound [82] or laser light pulses [83], reviewed elsewhere [73].…”
Section: Nucleation Temperaturementioning
confidence: 99%
“…37 It has been shown that intentional cavitation induced by a focused, pulsed laser can cause nucleation, although it should be noted that such cavities are preceded by plasma formation, for which photochemistry cannot be ruled out as the underlying mechanism. [38][39][40] A mechanism for NPLIN based on heating of impurity nanoparticles would explain a number of observations that are not readily explained by the polarization mechanism, which we summarize as follows.…”
Section: Particle Heatingmentioning
confidence: 99%
“…Similar thermodynamic considerations should also be relevant for the water-vapor interface during cavitation in the absence of lipids. In this regard, the present study may provide insight into the phenomenon of nucleation of ice during cavitation, also known as sono-crystallization, which has been proposed to explain experimentally observed nucleation of ice at the interface (43)(44)(45). Based on seminal work by Hickling (46) it is generally accepted that sonocrystallization is due to adiabatic compression by shock waves emitted from a bubble collapse and not from bubble expansion.…”
Section: Discussionmentioning
confidence: 71%